Contact with Mental Health Services After Acute Care for Self‐Harm Among Adults Released from Prison: A Prospective Data Linkage Study. Issue 5 (2nd May 2020) - Young, Jesse T.; Borschmann, Rohan; Heffernan, Ed; Spittal, Matthew J.; Brophy, Lisa; Ogloff, James R. P.; Moran, Paul; Armstrong, Gregory; Preen, David B.; Kinner, Stuart A.
Abstract : Objective: To determine the care pathway and rate and predictors of mental health care contact within seven days of discharge from acute care following self‐harm. Method: In a representative cohort of adults released from prisons in Queensland, Australia, we probabilistically linked person‐level, statewide ambulance, emergency department, and hospital records, both prospectively and retrospectively, and community mental health service and Medicare records prospectively, to baseline survey data. We fit multivariate modified log‐linked Poisson regression models to examine the association between sociodemographic, health, and criminal justice factors and mental health care contact after self‐harm. Results: Of 217 discharges from acute care following self‐harm, 55% ( n  = 119) received mental health care within seven days of discharge. Mental health care contact was associated with substance use disorder (adjusted relative risk (ARR) = 0.48; 95% CI: 0.27–0.85), dual diagnosis (ARR = 0.58; 95% CI: 0.41–0.82), physical health‐related functioning (ARR = 0.98; 95% CI: 0.97–0.99), being female (ARR = 1.39; 95% CI: 1.02–1.90), being identified as at risk of self‐harm by correctional authorities (ARR = 1.50; 95% CI: 1.07–2.09), and prior engagement with state‐funded mental health care (ARR = 1.55; 95% CI: 1.08–2.22). Conclusion: Our findings highlight the need to improve the integration of community mental health care for people who present to acute care following self‐harm with a recent history of incarceration, particularly for men and those with substance use disorder or dual diagnosis.